Mixed oxides from calcined layered double hydroxides for glycerol carbonate production to contribute to the biodiesel economy - Dalma, Argüello; Nancy, Bálsamo; Griselda, Eimer; Mónica, Crivello (Frontiers in Chemical Engineering, 2022)
The glycerol generated as a by-product in the biodiesel production could be used as a renewable raw material to economically promote the process. The catalytic conversion of glycerol to a product with higher added value, such as glycerol carbonate, has attracted great interest to the chemical, pharmaceutical, lithium battery industries, etc., due to its low toxicity, hydration capacity and biodegradation. The precursors of the catalysts, the layered double hydroxides materials, were synthesized by direct coprecipitation method to incorporate a third metal ion in addition to magnesium and aluminum ones. This method is the easiest regularly applied technique to design these low cost anionic nanoclay. The atomic percentage of Cu, Zn or Ni incorporated was 15% of the Mg load in the material. The synthesis atomic ratio, (M2++Mg2+)/Al3+, was a constant value of 3, where M represents the transition metal incorporated. The layered double hydroxides produced the corresponding mixed metal oxides by thermal decomposition. These materials have excellent properties for reactions catalysed by basic sites, high surface area, homogeneous cation dispersion and thermal stability. The physicochemical materials properties were characterized by XRD, N2 sorption, MP-AES, TPD-CO2, SEM and XPS. The mixed oxides were evaluated in the catalytic conversion of glycerol to glycerol carbonate. The addition of Cu, Ni or Zn on the matrix of Mg and Al produced changes in its physicochemical properties and mostly in the catalytic activity. The X ray diffractograms of the layered double hydroxides showed the typical characteristic structure of layers even with the metallic ions of Cu, Ni or Zn incorporated, due to the ionic radii are similar to the Mg one, 0.69Å, 0.73Å and 0.74Å, respectively. The mixed oxides obtained showed a high catalytic activity towards the conversion of glycerol to glycerol carbonate under mild reaction conditions, a 1:2 ratio of glycerol:ethylene carbonate and solvent free. Relative yields higher than 80% were obtained, attributable to an adequate distribution of basicity and textural parameters. The catalysts were used in successive reaction cycles without significant loss of their activity.